MOTIF KERJA SAMA PEMERINTAH MALAYSIA DENGAN PEMERINTAH KOREA SELATAN DALAM PROMOSI PRODUK HALAL DAN PARIWISATA RAMAH MUSLIM 2021 - Dita Natasha; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study discusses the motives for cooperation between the Malaysian government and the South Korean government in the halal industry. In 2021, Malaysia and South Korea signed an MoU that resulted in an agreement on the promotion of halal products and Muslim-friendly tourism. The purpose of this study is to explain and find out the reasons for the cooperation between the two countries in the halal industry. This study uses a liberalism perspective, with the level of nation-state analysis. This study also uses the theory of international cooperation and the concept of national interest. The method used in this study is a qualitative method with data collection techniques using literature studies and various literatures that refer to books, journals and sites on the internet. This study shows that the reason for this collaboration is because Malaysia sees a large potential market for halal products and Muslim-friendly tourism in South Korea. The Hallyu trend makes many Muslim foreign tourists visit South Korea so that the demand for halal products also increases. Not only that, Malaysia sees the potential for Muslim-friendly tourism in South Korea which still needs to be developed. Through this cooperation, the two countries can increase exports of halal products and hold training in the field of Muslim-friendly tourism. Keywords: Halal industry, Muslim-friendly tourism, International cooperation